Modos de beber em áreas indígenas no Mato Grosso do Sul: aproximações entre a psicologia social e perspectivas kaiowá e guarani - Moretti, Leandro Lucato (2017)
Alcoholic beverages and ways of drinking are present in the daily lives of the Kaiowá and Guarani and often, are related to several problems faced by these groups, such as internal violence among relatives. However, it should be understood that despite of the introduction of distilled beverages by settlers arriving in the territories traditionally occupied by the Kaiowá, there were already fermented beverages belonging to these groups that were consumed for different reasons based on cosmology and the ideal way of life. In this sense, in this work, it was adopted as a general objective to know, describe and register alcoholization processes and the different meanings elaborated internally regarding the consumption of beverages, more specifically in the aldeia Panambizinho. The method used here has an ethnographic inspiration, which allowed to approach the perceptions and perspectives of the Kaiowá and Guarani. From the different inputs in the field research, it was possible to perceive that drinking take on several potencies related to the well-being of these groups, such as sociability, body building and health, among others. Despite transformations and changes generated by the contact with the Western way of life, it is still possible to perceive permanences in the ways of drinking, which can be shaped as forms of resistance against the violence characteristic of this contact